Ebulin 1, a nontoxic novel type 2 ribosome-inactivating protein from Sambucus ebulus L. leaves. - Tomás Girbés; Lucı́a Citores; Rosario Iglesias; José M. Ferreras; Raquel Muñoz; M. Ángeles Rojo; Francisco Javier Arias; J. R. Gil García; Eduardo Méndez; Margarita Calonge (1993)
A novel type 2 ribosome-inactivating protein (RIP) that we named ebulin 1 has been isolated from leaves of Sambucus ebulus L. (Caprifoliaceae). In vitro ebulin 1 strongly inhibited protein synthesis by rabbit reticulocyte lysates, rat brain, and rat liver cell-free systems but did not affect in vitro plant nor bacterial protein synthesis. Ebulin 1 is composed of two subunits, a catalytic A subunit (M(r) 26,000) and a D-galactose-binding lectin B subunit (M(r) 30,000). Amino-terminal amino acid sequence homology revealed the novelty that the ebulin 1 A-chain shares a high degree of homology not with the A-chain of other type 2 RIPs but rather with the Cucurbitaceae type 1 RIP briodin S and the anti-human immunodeficiency virus type I proteins trichosanthin and TAP 29. Upon treatment with acid aniline the rRNA from ebulin 1-treated rabbit reticulocyte ribosomes released the RNA fragment which is diagnostic of RIP catalytic action. Ebulin 1 was nontoxic to mice up to 2 mg/kg of body weight and did not inhibit protein synthesis in cultured NHC human epithelial cells which are highly sensitive to ricin.